1987
DOI: 10.2307/3565496
|View full text |Cite
|
Sign up to set email alerts
|

How Much Do Weasels Shape Microtine Cycles in the Northern Fennoscandian taiga?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . Wiley-Blackwell and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Oikos. . 1987. How much do weasels shape microtine cycles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
210
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 267 publications
(224 citation statements)
references
References 35 publications
11
210
2
1
Order By: Relevance
“…Previously, many studies have focused on predatorvole interactions as the prime mechanism determining vole cycles (Hansson 1987;Henttonen et al 1987;Hanski et al 1993;Klemola et al 2000a). However, more recent evidence has suggested that changes in environment, including reductions in food quality, may also play a significant role (Agrell et al 1995;Turchin & Batzli 2001;Ergon et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, many studies have focused on predatorvole interactions as the prime mechanism determining vole cycles (Hansson 1987;Henttonen et al 1987;Hanski et al 1993;Klemola et al 2000a). However, more recent evidence has suggested that changes in environment, including reductions in food quality, may also play a significant role (Agrell et al 1995;Turchin & Batzli 2001;Ergon et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Rodents were trapped at PallasjĂ€rvi in the Pallas-YllĂ€s National Park in western Finnish Lapland (68u 309 N 24u 099 E) in September 1998. Bank vole densities in that year were typical (for long-term rodent studies at PallasjĂ€rvi, see, for example, Henttonen et al, 1987;Henttonen, 2000). For this study, bank voles were trapped alive and euthanized the same day, and tissue samples were stored in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…We considered seasonal variations, but this species is characterised by important multi-annual fluctuations in population density (at PallasjĂ€rvi Henttonen 2000;Tkadlec and Stenseth 2001). These fluctuations have been attributed to various factors including predation (at PallasjĂ€rvi Henttonen et al 1987;Lambin et al 2000;Hanski et al 2001;KorpimĂ€ki et al 2005), competition (Hansen et al 1999), or seasonality (Tkadlec and Zejda 1998;Saitoh et al 2003). All might influence the phenotypic characteristics of the population, directly through differential selection or indirectly through changes in the age structure and the related wear stages.…”
Section: Article In Pressmentioning
confidence: 99%